2017
DOI: 10.1111/jdi.12666
|View full text |Cite
|
Sign up to set email alerts
|

Role of vitamin D in energy and bone metabolism in postmenopausal women with type 2 diabetes mellitus: A 6‐month follow‐up evaluation

Abstract: Aims/IntroductionResting energy expenditure was associated with a serum bone turnover marker in postmenopausal women with type 2 diabetes (T2DMPW) in the present cross‐sectional study. To clarify the fundamental pathological factor for the correlation of bone metabolism and basal metabolism in type 2 diabetes, a 6‐month prospective follow‐up study was carried out with supplementation of vitamin D.Materials and MethodsA total of 44 T2DMPW were enrolled. The following factors were evaluated at the beginning and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 56 publications
0
5
0
1
Order By: Relevance
“…However, relatively limited data about the effect of vitamin D on BTMs are available. A prospective partial intervention study in postmenopausal women with T2DM shows that 25(OH)D was positively correlated with PINP, especially in patients taking alfacalcidol [53]. The MINOS study, a prospective study of 881 men aged 19-85 years, revealed that serum 25(OH)D was not associated with BTMs in men under 55 years of age (n = 286) [54].…”
Section: Journal Of Diabetes Researchmentioning
confidence: 99%
“…However, relatively limited data about the effect of vitamin D on BTMs are available. A prospective partial intervention study in postmenopausal women with T2DM shows that 25(OH)D was positively correlated with PINP, especially in patients taking alfacalcidol [53]. The MINOS study, a prospective study of 881 men aged 19-85 years, revealed that serum 25(OH)D was not associated with BTMs in men under 55 years of age (n = 286) [54].…”
Section: Journal Of Diabetes Researchmentioning
confidence: 99%
“…International guidelines recommend vitamin D supplementation for the prevention and/or treatment of osteoporosis and osteoporotic fractures in men and postmenopausal women[250-252], although recent findings bring into question the efficacy of vitamin D supplementation in preventing fractures or falls, or improving BMD[253]. Vitamin D supplementation was shown to increase bone formation markers[254] and reduce bone resorption markers[255] in postmenopausal women with T2D, not to affect bone turnover markers in patients with T2D and chronic kidney disease[256], and to preserve femoral neck BMD in men with prediabetes[257]. Few data are available about the effect of the use of osteoporosis medications in patients with diabetes.…”
Section: Perspectives: Possible Preventive and Therapeutic Approachesmentioning
confidence: 99%
“…However, no information is available for the optimal benefits of vitamin D supplementation regarding different dosages related to time of administration, subsequent influences on clinical outcomes, and mostly importantly, dosing regimen influences on fat mass and bone metabolism [2,12]. The roles of vitamin D in energetic metabolism are well known [15] and many obese children and adults present low blood concentrations of vitamin D [12]. Indeed, a number of observational studies documented a substantial role of vitamin D deficiency in etiopathogenesis of metabolic syndrome and other obesity-related complications.…”
Section: Introductionmentioning
confidence: 99%